-
m--m-a's m-1=a's m-1 power (a-1)4-a to the nth power - a to the n + 1st power + a to the n + 2nd power to a = -a to the nth power (1 + a-a).
7.(2x+y)²-9(x+2y)²=4x²+4xy+y²-9x²-36xy-36y²=-5x²-32xy-35y²=-(x+5y)(5x+7y)
8.n+1-3a to the nth power of a + n-1 power of 3a = n-1 power of a (n-3 to the nth power of a *n-1 power of a+3).
-
1. .m(a-b)+2(b-a)=(m-2)(a-b)2..
6x y -5x y = x y (6x-5y) to the m power --a m-1 = a m-1 * (a-1) 4.-a to the nth power - a to the n+1st power + a to the n+2nd power = a to the nth power * (a -a-1).
m+n+p)(1-x)
4q-4qp+2)(1-p)²
7.(2x+y)²-9(x+2y)²=(5x+7y)(-x-5y)
-
1.(m-2)(a-b)
M-1 to the power (A-1).
to the nth power (-1-a+a).
5.(m+n+p)(1-x)
6.(p-1)²(4qx(1-p)+2)
7.Is it wrong?
n-1 power (a-3a+3).
Check again, I may have made a mistake in the exam.
-
1.(a-b)(m-2)
5.(1-x)(m+n+p)
6.(1-p)*2(4q+2)
7.-(x+5y)(5x+7y)
to the n-1 power (a-3 to the n-power * a+3 to the n-1 power).
-
The story of Yueyang Lou is written with great ambitions.
-
A: 1Original.
2.Original. =[4(x+y)]^2-[5(x-y)]^2=(4x+4y+5x-5y)(4x+4y-5x+5y)=(9x-y)(9y-x)
3.Is 3(a+b) 2 missing a c on the left side of the question? It's 3C(A+B) 2, right?
Original. =3c[(a+b)^2-9c^2]
3c(a+b+3c)(a+b-3c)
4.Original. =(x+2)(x+4)+(x+2)(x-2)=(x+2)(x+4+x-2)
2(x+2)(x+1)
-
1 (x minus root number 7) multiplied by (x plus root number 7).
2 (x * root number 2 minus root number 3) multiplied by (x * root number 2 plus root number 3).
3 (a+b) to the nth power multiplied by (a+b-1) squared.
-
1, (x-y-2) (x-y a square b (x square + 4) (x-2) (x+2).
3. (4th power of x + 4th power of y) (square of x + square of y) (x+y) (x-y).
-
If the original formula can take a+b as x and 2b as y, then the original formula =x 2-2xy+y 2=(x-y) 2=(a+b-2b) 2=(a-b) 2
-
a+b)²-4b(a+b)+4b²
a²+2ab+b²-4ab-4b²+4b²a²-2ab+b²
a-b) Factorization of similar types of questions is also done in the same way First, all, ,
1.Knowing a=10000 and b=9999, find the value of a + b -2ab-6a + 6b + 9. >>>More
1.(x+2)(x-2)
2.=a squared (x-y) - b squared (x-y) = (a squared - b squared) (x-y) = (x-y) (a+b) (a-b). >>>More
Solution: Original formula = x 2 + 4x-12
x+6) (x-2) (cross method). >>>More
a^2×(b+c)+b^2×(a+c)+c^2×(a+b)+2abc
Idea analysis: Observe the structural characteristics of the above formula. >>>More